Gastrointestinal parasites of taricaya, Podocnemis unifilis (Troschel, 1848) (Testudines: Podocnemididae) from Iquitos, Peru - Sánchez, Nofre (2006)
Many Amazonian animals are a valuable food source, for the rural and urban people of the Peruvian forest. Their meat is called carne de monte, and is the third source of protein food in the region. Podocnemis unifilis (Yellow-spotted Amazon River turtle or taricaya) is utilized for both its meat and eggs. The efforts for restocking this reptile through breeding in semicaptivity and captivity, has allowed increasing the population, and now they are abundant. However, the breeding process had not taken into account the sanitary aspect, and this information is barely known in Peru. With the objective of identifying the parasitic fauna of the taricaya, the digestive tracts of 12 females (2 adults, 10 young) captured in the Pacaya Samiria National Reserve where examined. Different grades of parasitic infection were found in all turtles investigated. The parasites identified were the nematodes Serpinema amazonicus (100%) and Ancyracanthus pinnatifidus Diesing, 1934 (83%), and the trematode Nematophila grandis (Diesing, 1939), Travassos, 1934 (100%). Ancyracanthus pinnatifidus is a new record from Peru.